Performance enhancing strategies in sailing sports: beyond training and nutrition - Andrea Pagliaro; Anna Alioto; Carlo Rossi; Sara Baldassano; Patrizia Proia (Termedia Publishing House, 2024)
Purpose Sailing is a water sport comprising several disciplines distinguished by the type of boat and number of crew. The sailor must constantly accommodate the movement of the hull according to the weather conditions. The study aims to provide targeted guidance regarding training and nutrition for sailor athletes. Methods Complete and effective training requires a synergistic combination of sport-specific elements and strategies designed to improve overall strength. Extensive discussion has been made of the types of workouts aimed at improving performance and preventing injury. Results Our research findings revealed that even though sailors' training considers the development of strength, endurance, speed, balance, and coordination, which are necessary to counteract the continuous adaptations of posture to weather conditions, these athletes are exposed to the risk of injuries that predominantly affect the knee and lower back. Sailing is an aerobic/ anaerobic sport in which there are no explicit suggestions regarding the nutritional aspect and supplementation and what their contribution could be in improving performance. Conclusions We hypothesise that targeted training paths for sailing athletes and personalisation of nutritional suggestions by timing the intake of macro- and micronutrients as well as taking specific supplements, can reduce the risk of injury and better impact recovery and performance in this discipline.